The Role of Parental Beliefs in the Development of Interest and Importance Value of Mathematics and Literacy from Grade 7 to Grade 9 (International Journal of Gender, Science and Technology, 2015)
The present study examined how interest and importance values towards mathematics and literacy develop from grade 7 to grade 9 in comprehensive school, and to what extent does gender, as well as mothers’ and fathers’ child-specific ability beliefs predict the level and changes in these values. A total of 206 Finnish students (100 girls, 106 boys) were followed from grade 7 to grade 9, right before an important transition from compulsory comprehensive school to secondary education occurs in Finnish context. Students’ parents participated in the study when the students were at grade 7. The results of multivariate latent change models showed that the interest and importance values and the development of those in one particular subject were associated with each other. The role of mothers’ and fathers’ beliefs was different from each other and, in addition, the role was different in different subjects: mothers’ ability beliefs predicted students’ level of interest in mathematics and level of importance in literacy. However, fathers’ ability beliefs were found to predict the changes related interest and importance values in mathematics. The role of gender in students’ values was more evident in the case of literacy than in mathematics.